THE INFLUENCE OF LIFESTYLE, SERVICESCAPE, AND FOOD QUALITY ON CUSTOMER REVISIT INTENTION AT DECADE COFFEE SHOP - Therok, Francisca A.; Saerang, David P. E.; Wangke, Shinta J. C. (Universitas Sam Ratulangi, 2021)
Abstract: The growth of coffee house in Manado motivate the owner of Decade Coffee Shop to open a coffee shop that offers a calm and comfortable for the gathering of consumers with friends or relatives or just want to relax enjoying coffee. Revisit intention is described as the willingness of customer to come back to the same place or probability of them to repurchase a product from the same place. Revisit intention can be affected by so many factors, include lifestyle, servicescape, and food quality. The purpose of this study is to know the simultaneous and partial influence of lifestyle, servicescape, and food quality on customer revisit intention at Decade Coffee Shop. This research used multiple regression analysis with sample of 100 respondents. The result shows that lifestyle, servicescape, and food quality are simultaneously influence customer revisit intention. Servicescape and food quality have significant influence on customer revisit intention partially, meanwhile lifestyle has not have a significant influence on customer revisit intention. Based on the result, researcher suggest that the place should be always clean, well arranged, and have a good atmosphere to retaining the customers. The owner should keep their employees current performance like give a bonus or other reward that can be motivate the employee to work harder because it shows that they already done their job well by serving a delicious and well-presentation food for the customers. The last, Decade Coffee Shop should think about how to attract and drive the customers to spend their free time at Coffee Shop.Â Keywords: lifestyle, servicescape, food quality, customer revisit intention